In Vitro Dissolution Evidence for Sustained and Prolonged Release of Vitamin C in a Phosphatidyl Choline-Enriched Lipid Encapsulation. (7th June 2021) - Sharafi, Mastaneh; White, Tyler; Fowler, Kelli; Ewell, Kevin; Galvan, Noe; Alamdari, Nima
Abstract: Objectives: In vitro dissolution tests are valuable first-step tools in the development of bioavailable delivery systems, making it possible to assess the performance of novel technologies in releasing active ingredients through the amount dissolved in a dissolution medium. The objective of this study was to evaluate whether phosphatidyl choline-enriched lipid encapsulation releases the majority of vitamin C as ascorbic acid past the stomach in a standard in vitro dissolution procedure and to assess the release profile. Methods: A novel phosphatidyl choline-enriched lipid encapsulation that is solid at room temperature was tested for dissolution in a standard dissolution apparatus according to compendial United States Pharmacopeia methods, as per Good Manufacturing Practices for dietary supplements. One serving (included 1000 mg ascorbic acid) was placed into vessels containing simulated gastric fluid (0.1 M HCl) for 120 minutes then changed to simulated intestinal fluid (buffered 2% sodium lauryl sulfate, pH 6.8) for an additional 360 minutes. Aliquots were tested for ascorbic acid concentration at 8 time points by titration. The data was compared with 1000 mg of regular ascorbic acid in a capsule format. Results: The phosphatidyl choline-enriched lipid encapsulation released 36% of the vitamin C at 2 hours in the acid phase and released 56% at 3 hours, 67% at 4 hours, 85% at 6 hours and 98% at 8 hours in the intestinal phase. Regular vitamin C filled capsules released 100% of the vitamin C at 30 minutes. Conclusions: The dissolution results indicated that phosphatidyl choline-enriched lipid encapsulation can pass the stomach and release the majority of vitamin C in the small intestine. The encapsulation demonstrated a sustained and prolonged release of vitamin C over an 8 hour period. The release profile observed in this in vitro study suggests phosphatidyl choline-enriched lipid encapsulation may improve nutrient absorption and bioavailability which requires further testing including human clinical trials. Funding Sources: This study was supported by Lonza (Greenwood, SC) and Ritual (Natals Inc, Los Angeles, CA).